Hybrid control technique for vibroacoustic performance analysis of a smart doubly curved sandwich structure considering sensor and actuator layers. (June 2021) - Darvishgohari, Hamed; Zarastvand, MohamadReza; Talebitooti, Roohollah; Shahbazi, Rahmat
The present approach considers hybrid control strategy to reduce the amount of transmitted sound through a multilayered doubly curved sandwich shell equipped with piezoelectric layer and shunt circuit. The construction is composed of some piezoelectric actuator and sensor layers as an active controller as well as resistance–inductance shunt circuit as passive controller. In addition, a layer made of isotropic material is also sandwiched as a core. Firstly, in order to obtain the electromechanical equations of curved shell integrated with piezoelectric layers, Hamilton's principle, and shear deformation shallow shell theory are employed. After presenting the sound transmission loss of structure, the reliability of the formulation is checked by the aid of previous outcomes. In the following, the piezoelectric layers coupled with shunt circuit are employed to inspect the influence of these patches on the control of transmitted sound through structure. The results indicate that the shunt circuit is able to enhance the sound transmission loss at resonant frequency with no need source of energy. Since in designing the engineering structures, the transmitted noise control is important especially in the resonant frequency, the influence of using several parallel shunt circuits with each piezoelectric layer is also examined. It is shown that increment of the number of parallel shunt circuits implies substantial reduction of transmitted sound to the structure in the resonant frequency. Finally, the solution process is followed to study the effect of active control on the acoustic transmission. Then, it is found that employing the simultaneous active and passive controllers not only cause to reduce the transmitted noise in the resonant frequency but also make to improve the behavior of sound transmission loss in entire range of frequency.